2011
DOI: 10.1111/j.1365-2982.2011.01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of denervation at ileocecal junction and ileocecal resection in dogs

Abstract: Gastrocolonic response at the ICJ may require both intrinsic and extrinsic innervation. When ID was performed, CMMC ratio increased. As a result, intraluminal water absorption may have decreased. ID may be one of the causes of diarrhea after ICR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Colonic migrating motor complexes (CMMCs) are one of the major types of motor pattern that occur in the large intestine of a variety of mammals both in vivo (Ferre and Ruckebusch, 1985; Sarna, 1991; Morita et al, 2012) and in vitro (Wood, 1973; Fida et al, 1997; Bywater et al, 1998; Brierley et al, 2001; Powell and Bywater, 2001; Roberts et al, 2007, 2008; Heredia et al, 2009; Copel et al, 2013). CMMCs have also been reported in human colon in vivo (Hagger et al, 2003) and recently in the intact whole isolated human colon (Spencer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Colonic migrating motor complexes (CMMCs) are one of the major types of motor pattern that occur in the large intestine of a variety of mammals both in vivo (Ferre and Ruckebusch, 1985; Sarna, 1991; Morita et al, 2012) and in vitro (Wood, 1973; Fida et al, 1997; Bywater et al, 1998; Brierley et al, 2001; Powell and Bywater, 2001; Roberts et al, 2007, 2008; Heredia et al, 2009; Copel et al, 2013). CMMCs have also been reported in human colon in vivo (Hagger et al, 2003) and recently in the intact whole isolated human colon (Spencer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic denervation distal to the bowel resection is a crucial factor. In a study performed on dogs, Morita et al 21 found an increased rate of colonic migrating motor complexes and a reduced rate of colonic nonmigrating motoric complexes following intrinsic denervation of the colon. They found a clear relation between intrinsic denervation of the colon and diarrhea.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we were able to compare the effects of various reagents in the same animals. In this context, four to six dogs have been used in recent studies from our institution (Hayashi et al 2010;Sato et al 2010a) and other institutions (Dong et al 2005;Morita et al 2012;Yanai et al 2013).…”
Section: Discussionmentioning
confidence: 99%